Peran Apoteker dalam Meningkatkan Kepatuhan Pengobatan pada Pasien Rawat Jalan Tube - LUNGGUK HUTAGAOL; MITA RESTINIA; SESILIA ANDRIANI KEBAN (Fakultas Farmasi Universitas Pancasila, 2017)
Our previous study showed that one of risk factor may lead treatment failure on tuberculosis was non adherence. The current research was carried out to fi nd the role of pharmacist in increasing on medication adherence of tuberculosis outpatients. A non-randomized controlled study was conducted at one of government hospital in Jakarta during April 2015 to July 2015 using MMAS-8. Total sample were 108 patients that divided each group of 54 patients into experimental group who had education and control group without education. Mean of age were 36.93 (SD=15.02) of experimental group and 38.12 (SD=15.11) of control group. More than 50% respondents were male with education level of senior high school. Control group had higher adherence in pre education than post education (P<0.05). Meanwhile, medication adherence in experimental group of pre education was signifi cantly diff erent with post education, 1.94±1.65 vs 0.54±0.64 (P<0.05). There was no diff erence signifi cant of adherence between experimental group and control group in pre education. Furthermore after patients education had been applied experimental group’s adherence had higher than control group (P<0.05). The fi nding of the study may lead that impact of patient education by pharmacist result in better medication adherence.